State capture as a manifestation of the historic narrative of oligarchy in selected African Countries - Sebake, B. K. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
The history of state control is characterised by actions of the elites’ who influence the state power towards a specific direction of its benefits. This practice has generated political patronage growing into power elitism in African states, in which resources are channeled into private purse for capitalist reasons. The unforeseen governance-ills of state capture created political instabilities and divided the society in the post-colonial Africa. The impact of state capture often made the majority of African societies to survive under the ravages of poverty in the midst of the power game. The unintended consequences of the state capture is that, it may reverse the gains of a maturing democracy and in the efforts to restore the dignity of the African people through improved service delivery and poverty alleviation. This paper argues that the control of public resources is illegally diverted into private control by this arrangement. The worrisome factor is the manner in which this illegal and manipulative system has been institutionalised in some parts of the African states and they are protected for their wrong doings in the name of finding political correctness. The paper is a literature review in nature and primarily a qualitative reflection of the history of governance in African States in the quest to outline scotches of state capture. The focus areas are on historic and concept analysis of oligarchy, state capture analysis and its impact, capitalism as a colonised set-up of public service in Africa, institutional set-up of corruption, negative impact on African States. The paper aims to contribute towards researches in the scholarship of Public Administration and for solutions on governance-ills in African continent.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: State capture; Oligarchy; Democracy; Political power; Service delivery; Corruption; Oligarchy -- Africa; Africa -- Politics and government